(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Kidnapping is a major problem for many law enforcement agencies. The primary objective is to catch all the people behind this kind of illegal activity and protect the person from any threat to his surroundings; the primary target of a perpetrator is women; according to the Philippine National Police Anti-Kidnapping Group, every year, we are expecting a hundred cases of kidnapping in a different part of the Philippines which is the primary victim are women to ask for some ransom and favor in exchange of the life of a victim. Respondents assessed the impact of continuous kidnapping in Pasong Putik, Quezon City. Severe or long terms stress, trauma, neglect, cause of kidnapping in Pasong Putik, Quezon City, sleep problems, low mood, high levels of anxiety, and other mental health problems can make it difficult in daily life, Experiencing panic attacks, depression, and schizophrenia, Having problem with memory, reality thinking confusion and concentration. The discussion demonstrates the impact of continuous kidnapping in Pasong Putik Quezon City on how to address the problem encountered by the respondent, and here are some ways to promote and practice safety. Avoid posting your personal information or your home address, conduct free legal advice to the victim, Conduct a seminar about kidnapping at least once a month, Install more CCTV cameras on every corner of the street, And the last rank is Carry any self-defense weapon at all times, sharp object such as a ball pen or pepper spray has regarded as (Very Agree)